Estudo da qualidade da água e abastecimento da zona urbana de Belém (PA), aplicação à problemática existente no bairro do Jurunas - BRAZ, Vera Maria Nobre (Universidade Federal do Pará, 2022)
The present work aimed to evaluate the quality of the water consumed in Belém, mainly in areas where sanitary conditions were deficient. For this purpose, the Jurunas neighborhood was chosen as the study universe, which presents itself with extensive areas of "lowlands", lacking in sanitation. The water quality was verified through physical-chemical and bacteriological analyses. The analyzed samples were classified according to the potability standards of the World Health Organization, through a computer program. Trace elements such as Ni, Co, Cu, Cr, Pb, Mn and Al were also studied by themeelectric atomic absorption spectrometry, a study that had not been done before in the waters that supply the City. In the experimental phase, four samplings were carried out, distributed in the months of May, August, November 1983 and February 1984, so that the seasonal variations that might occur could be detected. The collections were carried out in ten points, representative of the entire neighborhood. In order to characterize the environment, aspects related to geology, geomorphology, climate, vegetation, soil and hydrology of the City were approached. On the other hand, considerations were made about the springs, the water treatment system and the supply and sewage networks. In particular, we sought to correlate the sanitary conditions of the lowlands with the occurrence of waterborne diseases. According to the results of the analytical determinations, it was verified that most of the physicochemical parameters studied were compatible with the potability standards. Exceptions were constituted, pH, conductivity, chlorides, iron and aluminum, whose values ​​extrapolated the recommended ones, mainly those referring to the month of November of 83, period in which there was a strong drought in the region, which caused salinization of the waters of the springs and of supply. Regarding the bacteriological parameters, 34% of the values ​​were outside the criteria recommended by the WHO, thus constituting one of the most significant problems detected in the analyzed waters. The results obtained were probably due to the conditions of the distribution network in the neighborhood, as well as the hygienic conditions in some collection points; the presence of bacteria in the water is the cause of numerous diseases, and some of their symptoms were detected in the population residing in the neighborhood, during the associated sampling.